ANALISIS PENGARUH DESENTRALISASI FISKAL TERHADAP AKSESABILITAS PENDIDIKAN DI INDONESIA PERIODE SEBELUM DAN SETELAH DESENTRALISASI FISKAL - Dayu Larasati; Hendra Saputra (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2014)
Fiscal decentralization carried out with the belief that local government understand the needs of people in the region better than the central government does. With a policy of fiscal decentralization, local government are expected to achieve a more equitable social welfare. This research was conducted because of the increasing demands of society that the government should pay attention to their needs, especially education that is now a major requirement for the community and even falls into one of national priorities . The conclusions of this study are : 1 increased own source revenue (PAD), general purpose grant (DAU) and special purpose grant (DAK) of education can increase educational spending by district/municipality local government ; 2. Increase spending on education by district/municipality local government can improve the accessibility of education by the public 3. The welfare of district/municipality can increase educational spending by district/municipality local government and accessibility of public education ; 4. In rich district/municipality, the increase in local government education spending has greater effect on increasing accesibility of public education than in poor district/municipality; 5. Fiscal decentralization policy can improve the accessibility of education by the community.